Exploring veterinarians’ perceptions of decision-making with clients in the context of providing access to veterinary care - Catherine N.H. Groves; Jason B. Coe; Cathy Bauman; Lauren E. Grant (PLoS ONE, 2026)
Veterinarian-client decision-making and its role in improving accessibility of veterinary care for all pets is an emerging topic in the veterinary field. The objective of the present study was to understand veterinarians’ perceptions and experiences engaging in decision-making with clients in the context of providing access to veterinary care. Semi-structured interviews were conducted with companion-animal veterinarians (n = 15), randomly sampled from across Ontario. Inductive thematic analysis was conducted on verbatim transcripts. Most participants worked strictly as a small-animal practitioner at a multi-vet practice, were women, and employed full-time. Four inductive themes relating to the primary study objective were identified: 1. discussing options helps address barriers to veterinary care, 2. veterinarians’ descriptions of presenting options differed, 3. veterinarians and veterinary-team members face challenges in presenting options to clients, and 4. a recognized shift is happening away from a singular “Gold Standard” option. All participants discussed the importance of options and shared that discussing options assists in addressing access barriers to veterinary care. Participants differed in their descriptions of what presenting options to clients meant. Descriptions included A) presenting all available options alongside risks, benefits, and other details; B) making a recommendation and discussing other options, if needed; or C) contextualizing options based on history gathered prior to discussion of options with the client. Participant-identified challenges regarding discussion of options included time constraints, client non-cooperation, and veterinarian bias. All participants referenced the term “Gold Standard”, with many acknowledging a shift away from this practice toward offering a range of options in support of providing access to veterinary care. Presenting options and working with clients to contextualize care offers a potential opportunity to increase access to veterinary care.